Ambulatory segmentary safenectomy - Chávez Reyes, Guillermo (2006)
Varicose veins disease of inferior members are a health problem in both sexs. The surgery procedure is important for its treatment. Goal: The research currently looking to identify results of ambulatory segmentary safenectomy and its complications. Material & methods: prospective, descriptive and analytic research in 27 patients with essential varicose veins of inferior members whom were treated by ambulatory segmentary safenectomy during January-December 2003. Results: The average age was 42 with median age of 39. The varicose veins disease were more frequently in female population. The complications were minimal with predominance of proximal segment (over the knee). Conclusions: The ambulatory safenectomy requiere less invasive boarding, without hospitalization, with minimal complications and good cosmetic results.